PENGARUH WORD OF THE DAY DAN WORDS GROUPING ACTIVITIES TERHADAP HASIL BELAJAR VOCABULARY SISWA KELAS VIII DI MTs.S BAHRUL ‘ULUM PESISIR SELATAN - Saputra, Bobi; Efendi, Efendi; Ramadhani, Ramadhani (STKIP Pesisir Selatan, 2021)
This study aims to determine the effect of Words of The Day and words grouping activities on the Vocabulary learning outcomes of grade VIII students at MTs.S Bahrul 'Ulum Pesisir Selatan. The research was conducted in class VIII MTs.S Bahrul 'Ulum, Pesisir Selatan Regency. This type of research is a quasi-experimental class using experimental class and control class. The research subjects taken were students in class VIII MTs.S Bahrul 'Ulum, Pesisir Selatan Regency. Data collection techniques that will be carried out in this study are tests and documentation. Data collection using student learning outcomes tests is intended to get an overview of the learning outcomes of groups of students taught using Words of The Day and word rouping activities against groups of students taught using conventional learning methods. Documentation is used to obtain data about the list of names of students who are the research subjects. The results in this study indicate that (1) that the Vocabulary learning outcomes of students using the Words of The Day learning method and word rouping activities are better than the learning outcomes of students using conventional learning methods with the value sig. (2-tailed) 0.020 < α 0.05, (2) there are differences in learning outcomes. Before and after students' Vocabulary groups used the Words of The Day learning method and word rouping activities with the value sig. (2-tailed) 0.002 < α 0.05.